First Indian at the South Pole: Sledge Odyssey to Antarctica - SEHRA, PARMJIT SINGH (SCHOOL SCIENCE, 2006)
ADAPTABILITY certificate: Thinking that the Russian doctor on board the ship ‘Viese’ sailing to Antarctica might be asking for my International Health Certificate, I promptly gave him that. But he smiled and remarked, “Wintering over the South Polar Ice-cap where the temperatures range from -40 to -90°C and the winds blow with speeds exceeding 200-300 km per hour is not a joke, my friend. Your certificate is meant only for the posh cities of the world.